2013
DOI: 10.1155/2013/876171
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Central Inhibition after Transcranial Magnetic Stimulation of Motor Cortex in Schizophrenia with Long-Term Antipsychotic Treatment

Abstract: Aims. Schizophrenia is a neuropsychiatric disorder associated with mental and motor disturbances. We aimed to investigate motor control, especially central silent period (CSP) in subjects with schizophrenia (n = 11) on long-term antipsychotic treatment compared to healthy controls (n = 9). Methods. Latency and duration of motor evoked potentials (MEPs) and CSPs were measured with the help of single pulse transcranial magnetic stimulation (TMS) and intramuscular electrodes. After stimulation of the dominant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Finally, 7 studies examined the relationship between TMSevoked muscular responses and medication dose in patients. 58,60,84,89,100,104,129 No significant correlation was reported between antipsychotic dose and RMT, AMT, MEP amplitude elicited by single suprathreshold stimuli, CSP duration or left dorsal premotor-right motor facilitatory connectivity. 58,84,89,100,104,129 Further, the degree of SICI and ICF was not related to the dose of antipsychotics 58,84,89 or benzodiazepines.…”
Section: Tms-emgmentioning
confidence: 94%
See 2 more Smart Citations
“…Finally, 7 studies examined the relationship between TMSevoked muscular responses and medication dose in patients. 58,60,84,89,100,104,129 No significant correlation was reported between antipsychotic dose and RMT, AMT, MEP amplitude elicited by single suprathreshold stimuli, CSP duration or left dorsal premotor-right motor facilitatory connectivity. 58,84,89,100,104,129 Further, the degree of SICI and ICF was not related to the dose of antipsychotics 58,84,89 or benzodiazepines.…”
Section: Tms-emgmentioning
confidence: 94%
“…In contrast, Daskalakis and colleagues 130 showed increased CSP duration in medicated patients compared to unmedicated patients, and similar CSP duration between medicated patients and healthy controls. Further, Ahlgren-Rimpilainen and colleagues 100 found that in the nondominant extremities (i.e., the nondominant hemisphere, abductor digiti minimi and tibialis anterior muscles), patients who were taking conventional antipsychotics had shorter mean first and total CSP duration compared to healthy controls and patients who were taking atypical antipsychotics; those taking atypical antipsychotics had the longest mean first and total CSP durations. According to the authors, 100 these findings were in line with the assumption that clozapine, which is an atypical antipsychotic, may normalize or even lengthen reduced central inhibition in schizophrenia.…”
Section: Tms-emgmentioning
confidence: 98%
See 1 more Smart Citation
“…If the interstimulus interval between the 2 pulses is long, i.e., 9-25 ms, a facilitatory effect is observed, referred to as intracortical facilitation (ICF) [ 40 , 43 , 45 56 ]. ICF can constitute more facilitation and weaker inhibition.…”
Section: Methodsmentioning
confidence: 99%
“…A previously early study, on the CSP in schizophrenia, revealed no significant differences in the duration of CSP between schizophrenic patients and controls [ 46 ]. However, a longer initial latency (onset latency) in treated patients was recorded [ 45 , 56 , 69 ]. Multiple studies reported a consistent shorter CSP in patients without medication effects (risperidone and olanzapine) [ 34 , 39 , 52 , 70 , 71 ].…”
Section: Methodsmentioning
confidence: 99%